A case report of pneumonic-type adenocarcinoma diagnosed by transbronchial cryobiopsy after the patient's death - Zhao, Qiquan (Medicine (Baltimore), 2021)
RATIONALE: Due to its nonspecific manifestations, pneumonic-type adenocarcinoma can be easily misdiagnosed as pneumonia, tuberculosis, or other diseases, especially in developing countries where many patients in the early stage refuse invasive examinations. Early recognition of pneumonic-type adenocarcinoma is essential. PATIENT CONCERNS: We report a case of pneumonia lung adenocarcinoma diagnosed by frozen lung biopsy after death. DIAGNOSES: A 75-year-old male patient was admitted to the hospital on April 24, complaining of 5 months of recurrent coughing, expectoration, and panting, and his symptoms had been worsening over the past month. INTERVENTIONS: After obtaining informed consent from the patient's family, transbronchial cryobiopsy was performed at the bedside. OUTCOMES: After a positive rescue, the patient died. Pathological examination indicated adenocarcinoma. LESSONS: At present, surgery is still the first choice for the treatment of pneumonic lung cancer, and early diagnosis can remove the tumor as much as possible. Transbronchial cryobiopsy can be used for the collection of pathological samples, especially for the early diagnosis of pneumonic lung cancer.